Psychological and Physiological Effects of the Mindful Lovingkindness Compassion Program on Highly Self-Critical University Students in South Korea - Noh, Seunghye; Cho, Hyunju (Frontiers in Psychology, 2020)
Objectives: Self-critical behavior is especially relevant for university students who face academic and nonacademic stressors, leading to negative outcomes such as mental distress and psychopathologies. To address this behavior, mindfulness and compassion are important factors to decrease self-criticism and ensure positive outcomes. This study examined the psychological and physiological effects of an intervention, the Mindful Lovingkindness Compassion Program (MLCP), on highly self-critical university students in South Korea. Methods: Thirty-eight university students with a high level of self-criticism were assigned to an MLCP group (n=18) or waitlist (WL) group (n=20). Self-report measures of self-criticism, self-reassurance, psychological distress, and other mental health variables were completed, and the physiological measure of heart rate variability (HRV) was conducted before and after the intervention with both groups. In addition, one- and three- month follow-up assessments were conducted using self-report measurements. Results: Compared to the WL group, participants in the MLCP group experienced significantly greater reductions in self-criticism and psychological distress, and a greater increase in self-reassurance, mental health, and HRV. The improvements in the self-report measures were maintained when assessed one and three months later. Conclusions: MLCP could be a promising intervention for alleviating self-criticism and increasing self-reassurance among self-critical individuals.